Strengthening Community Healthy Behavior to Support Tourism Area - Fariani Syahrul; Annis Catur Adi; Eny Qurniyawati; Siti Shofiya Novita Sari; Arina Mufida Ersanti; Rizma Dwi Nastiti; Aisyah Noer Auliyah Madani Pertiwi; Muamar Afdhal Mahendra; Arina Farmalabitta Annis; Ali Iqbal Tawakal; Wizara Salisa (Journal of Community Engagement in Health, 2024)
Kenjeran Beach Amusement Park is one of the beaches with a strategic area bordering the Madura Strait. In addition, Kenjeran Beach Amusement Park also provides several facilities that can be enjoyed by tourists. The results of observations, still found low personal hygiene of food vendors, not all food vendors provide trash bins, and tourists are still seen littering. Based on the results of the problem situation analysis, it is necessary to strengthen healthy behavior in the community around the tourist area. The targets of the activity were elementary school students around the Kenjeran beach tourism area in Surabaya City 113 students and food and beverage vendors in the Kenjeran beach tourism area 20 in number, using total sampling. The purpose of community service activities carried out to strengthen community healthy living behavior to support tourism areas in the Kenjeran Beach area, Surabaya. The implementation that has been carried out in this community service are education to elementary school children, education to food vendors, observation of the cleanliness of the tourist area observation of how to serve snacks and laboratory tests of microbial contamination in food/beverage snacks. Then to evaluate understanding after education by analyzing the mean value of pre-test and post-test. The results of this activity have provided education for elementary school students regarding clean and healthy living behavior in the area even though the average pre-test score of 6.15 decreased to 6.07 during the post-test. The socialization of safe and healthy snacks for food vendors in THP Kenjeran Lama has also been carried out with the pre-test score having an average of 5.2 then increased to 8.7 at the time of the post-test. Laboratory test results showed a very alarming condition, namely 88.89% of food-beverage samples were contaminated with microbes with various types of bacteria. Suggestions from the results of this activity are still the need for more intensive education to school children about the selection of snacks and diseases transmitted through food and beverages. There is still a need for assistance from food vendors in processing and serving food and drinks by sanitary hygiene standards.